SPRING is a Dedicated Licensing Factor for SREBP-Specific Activation by S1P - Hendrix, Sebastian; Tan, Josephine M. E.; Ndoj, Klevis; Kingma, Jenina; Valiloo, Masoud; Zijlstra, Lobke F.; Ottenhoff, Roelof; Seidah, Nabil G.; Loregger, Anke; Kober, Daniel L.; Zelcer, Noam (Molecular and cellular biology, 2024)
SREBP transcription factors are central regulators of lipid metabolism. Their proteolytic activation requires ER to the Golgi translocation and subsequent cleavage by site-1-protease (S1P). Produced as a proprotein, S1P undergoes autocatalytic cleavage from its precursor S1P to mature S1P form. Here, we report that SPRING (previously C12ORF29) and S1P interact through their ectodomains, and that this facilitates the autocatalytic cleavage of S1P into its mature S1P form. Reciprocally, we identified a S1P recognition-motif in SPRING and demonstrate that S1P-mediated cleavage leads to secretion of the SPRING ectodomain in cells, and in liver-specific knockout (LKO) mice transduced with AAV-mSpring. By reconstituting SPRING variants into SPRING cells we show that the SPRING ectodomain supports proteolytic maturation of S1P and SREBP signaling, but that S1P-mediated SPRING cleavage is not essential for these processes. Absence of SPRING modestly diminishes proteolytic maturation of S1P and trafficking of S1P to the Golgi. However, despite reaching the Golgi in SPRING cells, S1P fails to rescue SREBP signaling. Remarkably, whereas SREBP signaling was severely attenuated in SPRING cells and LKO mice, that of ATF6, another S1P substrate, was unaffected in these models. Collectively, our study positions SPRING as a dedicated licensing factor for SREBP-specific activation by S1P.